Implementasi Bauran Promosi Untuk Menguatkan Branding Destinasi Wisata Nusa Penida, Kabupaten Klungkung (Studi Kasus Dinas Pariwisata Kabupaten Klungkung) (Jurnal Destinasi Pariwisata, 2025)
The purpose of this research is to identify the elements of identity and branding value of the tourism destination in Nusa Penida, Klungkung Regency, and to analyze the promotion mix of the campaign by the Klungkung Regency Tourism Office to strengthen the destination branding of Nusa Penida. Data were collected through observation, interviews, documentation, and literature studies. Informants were determined using two types of sampling: initial informants and key informants. The data were analyzed using a descriptive qualitative method. The results show that elements of the promotion mix, including advertising, sales promotion, personal selling, and public relations, have been implemented through various campaign forms. However, the implementation still faces several challenges, such as low stakeholder integration, underutilization of digital media, and limited innovation in promotional content. The branding of "The Blue Paradise Island" holds great potential to strengthen the destination’s identity, yet it requires a more integrated communication strategy that is adaptive to digital tourism trends. This study recommends cross-sector collaboration and the enhancement of digital promotion capacity to achieve effective promotion mix implementation and long-term branding success.